2011
DOI: 10.1038/aps.2010.237
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide inhibits the proliferation of cells from lymphocytic leukemic cell lines in association with downregulation of NF-κB activity and miR-16-1*

Abstract: Aim: To examine the effects of triptolide (TPL) on T-cell leukemia cells and identify their underlying mechanisms. Methods: The cytotoxicity of TPL was assessed by MTT assay. Cell apoptosis was determined using annexin V and DAPI staining and analyzed by flow cytometry or fluorescence microscopy. The activation of caspase pathways and the expression of nuclear factor κB (NF-κB) p65 were examined by Western blotting. Differences in microRNA (miRNA) expression in Molt-4 and Jurkat cells before and after TPL trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…It has been reported to have pharmacological and biochemical properties in the treatment of rheumatoid arthritis and several other autoimmune and inflammatory diseases, including immune complex nephritis and systemic lupus erythematosus (Lu et al, 2011). Besides, triptolide has been shown to have antitumor properties in a variety of human tumor cells via inhibiting cell proliferation and inducing apoptosis (Mujumdar et al, 2010;Meng et al, 2011;Wu et al, 2011). Despite the recognized potent antitumor activity of triptolide, our knowledge regarding its mechanisms of action is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to have pharmacological and biochemical properties in the treatment of rheumatoid arthritis and several other autoimmune and inflammatory diseases, including immune complex nephritis and systemic lupus erythematosus (Lu et al, 2011). Besides, triptolide has been shown to have antitumor properties in a variety of human tumor cells via inhibiting cell proliferation and inducing apoptosis (Mujumdar et al, 2010;Meng et al, 2011;Wu et al, 2011). Despite the recognized potent antitumor activity of triptolide, our knowledge regarding its mechanisms of action is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [14] also found that triptolide inhibits global transcription in cancer cells by induction of phosphorylation and subsequent proteasome-dependent degradation of RNA polymerase II (Rpb1), resulting in global gene transcription. Meanwhile triptolide's anti-proliferative and proapoptotic effects have been reported as being caused by the inhibition of nuclear factor-kappaB (NF-κB) and nuclear factor of activated T-cells-mediated (NFAT-mediated) transcription and the suppression of HSP70 expression [15][16][17] . In this report, we demonstrate for the first time that LLDT-67, a novel derivative of triptolide, has a potent and specific effect on the expression of NGF in astrocytes in vitro and in vivo, which suggests that LLDT-67 can potentially serve as a neuroprotective agent in the treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they demonstrated that As 2 O 3 reduced the expression of let-7d and miR-766 by degrading PML and inhibiting PML body recycling. In fact, accumulating evidence is revealing an important role of miRNAs not just in anticancer drug resistance but in drug action [47][48][49][50][51][52][53][54][55][56]. More importantly, these emerging data provide the basis for the study and development of novel therapeutic strategies targeting miRNAs in hematological malignancies.…”
Section: Mirnas Regulate Cell Apoptosis-related Proteinsmentioning
confidence: 99%